Advanced Placement: Access Not Exclusion - Camara, Wayne J.; Dorans, Neil J.; Morgan, Rick; Myford, Carol (Education Policy Analysis Archives, 2000)
Lichten (2000) argues that increased access to AP courses in high schools has led to a decline in AP quality. He uses a mix of actual data, inaccurate data, and fabricated data to support this hypothesis. A logical consequence of his argument is that a reduction in the availability of AP courses will lead to an improvement in AP quality. In this paper, we maintain that his thesis is flawed because he confounds quality with scarcity. In contrast to his narrow conception of quality, quality in the AP context is subject- specific and multifaceted, embracing course content, the teacher, the student as well as the exam. Increased access will not diminish quality. Instead, increased access exposes students to college-level course material, encourages teachers to expand their knowledge domains, serves as a lever for lifting curriculum rigor, and provides students with the opportunity to experience the challenges associated with advanced placement in college.